2020
DOI: 10.7150/thno.43163
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-derived small extracellular vesicles can signal eNOS activation in cardiac microvascular endothelial cells to protect against Ischemia/Reperfusion injury

Abstract: Rationale: The crosstalk between cardiac microvascular endothelial cells (CMECs) and cardiomyocytes (CMs) has emerged as a key component in the development of, and protection against, cardiac diseases. For example, activation of endothelial nitric oxide synthase (eNOS) in CMECs, by therapeutic strategies such as ischemic preconditioning, plays a critical role in the protection against myocardial ischemia/reperfusion (I/R) injury. However, much less is known about the signals produced by CMs that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 72 publications
(130 reference statements)
1
37
0
1
Order By: Relevance
“…In our recent experiment where ex vivo, in vivo, and in vitro settings of I/R were used, we identi ed the signals produced by cardiomyocytes that can regulate cardiac microvascular endothelial cells biology during myocardial I/R injury. We found that cardiac microvascular endothelial cells-derived eNOS activity was required for the cardioprotection of TXL, [44] which again con rmed the mechanism of TXL in the treatment of AMI.…”
Section: Discussionsupporting
confidence: 69%
“…In our recent experiment where ex vivo, in vivo, and in vitro settings of I/R were used, we identi ed the signals produced by cardiomyocytes that can regulate cardiac microvascular endothelial cells biology during myocardial I/R injury. We found that cardiac microvascular endothelial cells-derived eNOS activity was required for the cardioprotection of TXL, [44] which again con rmed the mechanism of TXL in the treatment of AMI.…”
Section: Discussionsupporting
confidence: 69%
“…The studies conclude that MSC-derived exosomes harbor all necessary enzymes that are required for the generation of ATP ( 165 , 166 ). The report also suggest that exosome treatment leads to the reduction in systematic inflammation in mice model after treatment with myocardial I/R ( 167 ) ( Figure 3 ). Thus, MSC-derived exosomes could be a powerful therapeutic solution for patients diagnosed with acute myocardial infarction ( 167 ).…”
Section: Stem Cellsmentioning
confidence: 82%
“…The report also suggest that exosome treatment leads to the reduction in systematic inflammation in mice model after treatment with myocardial I/R (167) (Figure 3). Thus, MSCderived exosomes could be a powerful therapeutic solution for patients diagnosed with acute myocardial infarction (167). The cardiac progenitor cells plays crucial role in angiogenic and cardiogenic properties in high-glucose conditions in both in vitro and animal models (168).…”
Section: Beneficial Role Of Stem Cell-derived Exosomes In Cvdmentioning
confidence: 99%
“…Upon transfer to cardiac microvascular endothelial cells, the internalized exosomes augment glucose uptake, glycolytic activity and pyruvate synthesis in endothelial cells [ 132 ]. In addition, cardiomyocyte-derived exosomes activate eNOS, which is responsible for nitric oxide production in endothelial cells, conferring protection against ischemia/reperfusion injuries [ 133 ]. This metabolic cross-talk also occurs between endothelial cells and immune cells.…”
Section: Exosome-mediated Remodeling Of Endothelial Gene Expressiomentioning
confidence: 99%